Management of Long-Segment and Panurethral Stricture Disease. (8th December 2015) - Martins, Francisco E.; Kulkarni, Sanjay B.; Joshi, Pankaj; Warner, Jonathan; Martins, Natalia
Abstract : Long-segment urethral stricture or panurethral stricture disease, involving the different anatomic segments of anterior urethra, is a relatively less common lesion of the anterior urethra compared to bulbar stricture. However, it is a particularly difficult surgical challenge for the reconstructive urologist. The etiology varies according to age and geographic location, lichen sclerosus being the most prevalent in some regions of the globe. Other common and significant causes are previous endoscopic urethral manipulations (urethral catheterization, cystourethroscopy, and transurethral resection), previous urethral surgery, trauma, inflammation, and idiopathic. The iatrogenic causes are the most predominant in the Western or industrialized countries, and lichen sclerosus is the most common in India. Several surgical procedures and their modifications, including those performed in one or more stages and with the use of adjunct tissue transfer maneuvers, have been developed and used worldwide, with varying long-term success. A one-stage, minimally invasive technique approached through a single perineal incision has gained widespread popularity for its effectiveness and reproducibility. Nonetheless, for a successful result, the reconstructive urologist should be experienced and familiar with the different treatment modalities currently available and select the best procedure for the individual patient.